Design and Development of a Telerehabilitation Self-Management Program for Persons with Chronic Lower Limb Swelling and Mobility Limitations: Preliminary Evidence - Becky L. Faett; Mary Jo Geyer; Leslie A. Hoffman; David M. Brienza (Hindawi Limited, 2012)
This paper describes design and development of a self-management program, delivered by telerehabilitation (TR), to address the problem of chronic lower limb swelling in persons with limited mobility. The 18.6 million persons with limited mobility in the USA are at increased risk for chronic lower limb swelling and related secondary complications, including cellulitis and skin ulcers. Over time, chronic swelling often progresses to lymphedema, an incurable condition requiring lifelong care. Without successful self-management, lymphedema and its related complications inevitably worsen. Access and adherence to appropriate treatment are challenging for persons with limited mobility. Program development involved a structured process to establish content validity (videos and manuals), readability, suitability, and selection of a TR platform to deliver the educational program. Our goal was to develop a program that would engage patients in self-management skills. The TR software platform chosen, Versatile and Integrated System for Telerehabilitation (VISYTER) was designed to facilitate face-to-face delivery of an interactive home-based self-management program via the internet in real time. Results demonstrated validity of the educational program and ease of use with TR. Future plans are to evaluate ability of this approach to promote self-management skills, home monitoring, and improved management of persons with lymphedema and limited mobility.